Pearl Harbor [videorecording (DVD)] - Affleck, Ben, 1972-; Hartnett, Josh, 1978-; Beckinsale, Kate; Gooding, Cuba, Jr., 1968- (Touchstone Home Video, 2001)
Two childhood best friends, Rafe and Danny, grow up wanting to fly planes. When Rafe gets the chance to join the Royal Air Force during World War II, he takes it, leaving his new love, Evelyn, a dedicated Navy nurse, and Danny, also a pilot, behind. Danny and Evelyn are transferred separately to the idyllic paradise of Hawaii, where they eventually meet through a connection to Rafe, who has been declared missing. But just as the love triangle begins to get complicated, Dec. 7, 1941 arrives, changing all of their lives forever.